The euro as a proxy for the classical gold standard? Government debt financing and political commitment in historical perspective - Andreas Hoffmann (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2013)
[Introduction] In spite of the recent troubles in the euro area, Jesus Huerta de Soto (2012), a famous proponent of the gold standard, argues that the euro should be considered a 'second best to the gold standard' and is worth being preserved. From a classical liberal point of view, he sheds some light on the euro's similarities with the gold standard and on some important advantages of the currency union over its alternative, flexible exchange rates in Europe. According to Huerta de Soto (2012), the main advantage of the introduction of the common currency is that - like when 'going on gold' - European governments have given up monetary nationalism. Like the gold standard, the euro limits state power as it prevents national central banks from manipulating exchange rates and inflating away government debt. Currently, he argues, the common currency - like previously the gold standard - forces important reforms and/or spending cuts upon the countries of the euro area that face severe debt and structural problems. In this respect, the euro should be seen as 'a proxy for the gold standard'. In this policy paper, I attempt to address some similarities and differences in the institutional framework of the classical gold standard (1880 - 1912) and the European Monetary Union (EMU) (1999 - ) that affect government debt financing and the way in which countries react to crisis. I argue that - in line with Huerta de Soto (2012) - giving up monetary nationalism and committing to the rules of either the gold standard or EMU initially restricted the scope of state action. Therefore, the euro - like previously the gold standard - provided some (fiscal) policy credibility. Fiscal policy credibility was the main determinant of capital market integration and low government borrowing costs in Europe under both systems. But in contrast to Huerta de Soto (2012), I shall emphasize that neither the gold standard, nor the euro itself force reforms and spending cuts upon countries that face crisis and debt problems. The political commitment to the monetary systems determines the willingness to reform or cut spending and therewith fiscal policy credibility in crisis periods: (...)
Keywords: 330